Sex hormones and metabolic syndrome in children and adolescents - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2009)
Cardiovascular risk starts early in life, yet the patterns of changes in metabolic syndrome (MS) during puberty and normal development have not been completely defined. Sex hormones are shown to play a pivotal role in the modulation of insulin resistance and MS. Our aim is to clarify the relation between sex hormones and MS in normal children and adolescents. This is a cross-sectional study of 365 (8-12 and 14-18 years old) school students. We analyzed the associations of sex hormones (testosterone, free androgen index, estradiol, free estradiol index [FEI], and sex hormone-binding globulin [SHBG]) with cardiovascular risk factors and MS. Prevalence of MS varied depending on the definition, and 33 (9%) students had MS based on at least 1 definition of MS. Frequency of MS doubled among 14- to 18-year-old adolescents compared with 8- to 12-year-old children (12.4% vs 5.6%, P = .02). Adolescent boys and girls with MS had significantly lower SHBG levels compared with controls. Adolescent boys with MS also had significantly higher FEI levels compared with controls. Logistic regression analysis was performed to find the predictors of MS. Among covariates of age, estradiol, testosterone, free androgen index, and FEI, SHBG was the only significant predictor of MS (B = -0.3, odds ratio = 0.8, 95% confidence interval for odds ratio are 0.64 and 0.92, P = .005, Nagelkarke R-2 = 0.48) in adolescent boys. In conclusion, sex hormone levels and androgen/estrogen balance may play an important role in determining MS and future cardiovascular risk among children and adolescents. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: MASS-SPECTROMETRY ASSAY; INSULIN SENSITIVITY; BLOOD-PRESSURE; BINDING GLOBULIN; TURKISH CHILDREN; GLUCOSE; OBESITY; RISK; TESTOSTERONE; LEVEL